Impacts of Different Exposure Scenarios on Transcript Abundances in Danio rerio Embryos when Investigating the Toxicological Burden of Riverine Sediments - Bluhm, Kerstin (Public Library of Science, 2014)
PURPOSE: Recently, a proof-of-concept study revealed the suitability of transcriptome analyses to obtain and assess changes in the abundance of transcripts in zebrafish (Danio rerio) embryos after exposure to organic sediment extracts. The present study investigated changes in the transcript abundance in zebrafish embryos exposed to whole sediment samples and corresponding organic extracts in order to identify the impact of different exposure pathways on sediment toxicity. MATERIALS AND METHODS: Danio rerio embryos were exposed to sublethal concentrations of three sediment samples from the Danube River, Germany. The sediment samples were investigated both as freeze-dried samples and as organic extracts. Silica dust and a process control of the extraction procedure were used as references. After exposure, mRNA was isolated and changes in profiles of gene expression levels were examined by an oligonucleotide microarray. The microarray results were compared with bioassays, chemical analysis of the sediments and profiles of gene expression levels induced by several single substances. RESULTS AND DISCUSSION: The microarray approach elucidated significant changes in the abundance of transcripts in exposed zebrafish embryos compared to the references. Generally, results could be related to Ah-receptor-mediated effects as confirmed by bioassays and chemical analysis of dioxin-like contaminants, as well as to exposure to stress-inducing compounds. Furthermore, the results indicated that mixtures of chemicals, as present in sediment and extract samples, result in complex changes of gene expression level profiles difficult to compare with profiles induced by single chemical substances. Specifically, patterns of transcript abundances were less influenced by the chemical composition at the sampling site compared t the method of exposure (sediment/extract). This effect might be related to different bioavailability of chemicals. CONCLUSIONS: The apparent difference between the exposure scenarios is an important aspect that needs to be addressed when conducting analyses of alterations in the expression level of mRNA.